KEJAHATAN KEKERASAN SEKSUAL (PERKOSAAN) DITINJAU DARI PERSPEKTIF KRIMINOLOGI - Made Dwi Kristiani (University of Udayana, 2014)
This study aims to describe and analyze in depth abaout sexual violence (rape) from persepektive of criminology. The methods that are in the form of normative research approach conceptually, with the study of documents as well as primary and secondary legal materials. Arrangements regarding crimes of sexual violence (rape) subject to the provisions of Article 285 of the Penal Code which has elements that must be met, one of which is the absence of violence. Any element of violence is an element that distinguishes the crime of rape with another morality set forth in Penal Code. In the perspective of criminology that really is not an element of violence that will be the main point, but the element of consent. Elements of consent is a decisive and qualify an act as rape or not. In addition,it also examined the factors causing crimes of sexual violence (rape) and mitigation efforts.